Risk assessment of the use of corrugated metal sheets for construction of road soil-shell structures - Mistewicz, Marek (Roads and Bridges - Drogi i Mosty, 2019)
The process of construction involves a risk of non-compliance of the construction works with the basic requirements of both Polish and European regulations. In order to mitigate the consequences of events related to the above-mentioned risk the products are subject to standardisation or technical evaluation prior to their placement on the market. The risk assessment methods are designed to identify the essential characteristics of construction products by analysing their effect on compliance of the construction works in which they are incorporated with the basic requirements. This article presents risk assessment related to incorporation in the works of a set of corrugated metal sheet products designed for construction of road bridges, overpasses and tunnels. An original qualitative method of risk assessment related to incorporation of a construction product in the works was conceived and its usefulness was confirmed. It has been demonstrated that while it is indispensable to carry out the risk assessment at the technical assessment stage, it is not, however, sufficient for efficient managing the risk of placing construction product on the market. W procesie budowlanym występuje ryzyko niespełnienia przez wznoszone obiekty podstawowych wymagań przepisów prawa obowiązującego w Polsce i w Europie. Aby ograniczyć skutki zdarzeń związanych z tym ryzykiem wymaga się, aby stosowane w budownictwie wyroby podlegały normalizacji albo ocenie technicznej przed wprowadzeniem ich do obrotu rynkowego. Metody oceny ryzyka służą do wyselekcjonowania zasadniczych charakterystyk wyrobu budowlanego, na podstawie analizy ich wpływu na spełnienie podstawowych wymagań przez budowle, w które wyrób ma zostać wbudowany. W artykule przeprowadzono ocenę ryzyka stosowania zestawu wyrobów, wykonanych z metalowych blach falistych, przeznaczonych do budowy mostów, wiaduktów i tuneli drogowych. Opracowano autorską metodę jakościową oceny ryzyka w przypadku stosowania wyrobów budowlanych i potwierdzono jej przydatność. Wykazano, że ocena ryzyka na etapie opracowania oceny technicznej jest warunkiem koniecznym, jednak niewystarczającym do skutecznego zarządzania ryzykiem związanym z wprowadzaniem do obrotu rynkowego wyrobów budowlanych.